Efektivitas Program E-Tilang Dalam Penindakan Pelanggaran Lalu Lintas Di Polres Karawang - Exaudio Palti Raja Hasibuan (Indonesian Journal of Police Studies, 2020)
This research was conducted upon the findings that researcher discovered when conducting the third level or sixth-semester work training at the Karawang Regional Police. The researcher found that there are problems within the E-ticketing programme that prompt the traffic corps officers to spend more time in the implementation, in contrast to the time utilised when implementing the conventional ticketing. This research was made with the aim to gain an understanding and find the solution to the problems that centre around the E-ticketing programme at Karawang Regional Police Station. Thus, the researcher used qualitative research methods, research literature, and conceptual literature to investigate the problems mentioned. Research references are in correlation to the E-ticketing programme. For this research, the theories employed are management theory and swot analysis theory. As for the conceptual model, the concept of effectiveness, E-ticketing and traffic violations were used. The data collection of this research was obtained from forum group forums, observations, document studies, and interviews. The presentation uses data analysis techniques. The rising number of problems that the officers come across during the implementation of the E-ticketing programme made the programme ineffective. In spite of that, the integrity and the enthusiasm of the officers in supporting the Traffic Corps programme made the programme sustains and operates for the last two years at the Karawang Regional Police Station. Internal evaluation found that there needs to be an improvement in the resources, enhancement in the infrastructure, and adjustment of personnel. As well as an increase in the public awareness and support from other related organisations for the external evaluation. The application of these two evaluations will cause the E-ticketing programme to operate better, and also becoming the solution in order for the traffic corps officers to no longer encounter any problems regarding to the E-ticketing programme.